THE EFFECT OF DIFFERENT PRE-SOWING TREATMENTS ON BREAKING SEED DORMANCY IN BAOBAB (Adansonia digitata L.) PLANT - DALHA ABUBAKAR, KABIRU; Musa, D. D.; Garba, N. H.; Mubarak, I. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Seed germination of baobab has necessitated with quiescence and hard seed coat impermeable to water and gases. It faces a high risk of extinction due to lack of regeneration. An experiment was carried out to investigate the effect of pre-sowing treatment techniques on seed germination of Baobab. Pot trials were conducted during 2021 dry season at Biological garden, Department of Plant Science and Biotechnology, Faculty of Life Science, Federal University Dutsin-Ma, Katsina State using completely randomized design (CRD). Seeds were subjected to four different concentrations of sulphuric acid, hot water, cold water, physical treatment and untreated seed as control and were analyzed independently to obtain the best treatment periods. Total of nine hundred and sixty (960) viable seeds were surface sterilized in 1.0% Sodium-hypochlorite (NaOCl) for 1 minute and rinsed three (3) times in sterile distilled water. 20 viable seeds were sown for each polypot. Physical pre-sowing treatment with full-sided scarification and treatment with hot water for 10 minutes produces the highest germination percentage (95.00%) and early seedling emergence (7th day after sowing). Seeds soaked in cold water for 8.00 hours gave the least mean days of seedling emergence (6th day after sowing) when compared to other treatments. These results suggested that full side scarification, soaking seed in hot water for 10 minutes and  cold water for 8.00 hours were optimum in breaking seed dormancy in Baobab and the techniques could be apply prior to planting to improve germination performance.